Perlindungan Hukum Terhadap Para Investor Asing di Indonesia Terkait Pengaruh Investasi Asing Bagi Laju Pertumbuhan Ekonomi di Bali - Valentino Junior Coumans (Jurnal Analogi Hukum, 2024)
Legal protection is a key cornerstone in maintaining the country's stability amidst the complexity of economic and legal twists. As a motor of prevention and enforcement, these protections guide foreign investment through the complex twists and turns of corporate law and capital markets, acting as a protective helmet in economic growth. Foreign investment, the engine of economic growth, faces potential disputes with the GoI, requiring protection from breaches of contract and policy. Political risk, economic crisis, and changing monetary tides are challenges on the investment trajectory. Providing guarantees in foreign investment in Indonesia is key to protecting investors and accelerating investment flows, creating a tense competition in the economic sphere. With a long history of foreign investment, these investments are expected to contribute positively to the economy, transfer knowledge, and improve welfare. Legal protection for foreign investors in Bali is crucial amidst the positive and negative impacts, driving the huge need for foreign investment.